2023
DOI: 10.1001/jama.2023.21407
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Vitamin C for Patients Hospitalized With COVID-19

Simin  Florescu,
Delia Stanciu,
Mihaela  Zaharia
et al.

Abstract: ImportanceThe efficacy of vitamin C for hospitalized patients with COVID-19 is uncertain.ObjectiveTo determine whether vitamin C improves outcomes for patients with COVID-19.Design, Setting, and ParticipantsTwo prospectively harmonized randomized clinical trials enrolled critically ill patients receiving organ support in intensive care units (90 sites) and patients who were not critically ill (40 sites) between July 23, 2020, and July 15, 2022, on 4 continents.InterventionsPatients were randomized to receive v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 29 publications
(55 reference statements)
0
26
0
Order By: Relevance
“…The Original Investigation titled “Intravenous Vitamin C for Patients Hospitalized With COVID-19: Two Harmonized Randomized Clinical Trials,” published on November 14, 2023, has been updated to fix the spelling of names in a supplement (Alessandro Belletti, Alessandra Bonaccorso, Claudia Costantino, Ashlish Dawda, Pierre-Yves Egreteau, Nasir Khoso, Sven Laudi, Juan Martin-Lazaro, Jack Richecoeur, L. Roebers, Giovanna Russelli, Patrica Thompson, and Harald Verheij are the correct spellings). This article was corrected online.…”
mentioning
confidence: 82%
“…The Original Investigation titled “Intravenous Vitamin C for Patients Hospitalized With COVID-19: Two Harmonized Randomized Clinical Trials,” published on November 14, 2023, has been updated to fix the spelling of names in a supplement (Alessandro Belletti, Alessandra Bonaccorso, Claudia Costantino, Ashlish Dawda, Pierre-Yves Egreteau, Nasir Khoso, Sven Laudi, Juan Martin-Lazaro, Jack Richecoeur, L. Roebers, Giovanna Russelli, Patrica Thompson, and Harald Verheij are the correct spellings). This article was corrected online.…”
mentioning
confidence: 82%
“…In our collective clinical experience, we frequently observe patients in the intensive care unit administered this vitamin solution for 5 to 7 days. Although we recognize that the vitamin C doses in the LOVIT, LOVIT-COVID, and REMAP-CAP studies were higher, we believe there now exist concerns about the potential deleterious effect of co-administering large doses of vitamin C when the primary aim is thiamine replenishment.…”
mentioning
confidence: 96%
“…To the Editor The recently published REMAP-CAP and LOVIT-COVID studies tested the hypothesis that the administration of high-dose vitamin C (ascorbic acid) increases the number of days patients are alive and free from organ support. However, these studies were terminated early when statistical triggers for harm and futility were met. In addition, the earlier LOVIT study found harm from high-dose vitamin C and a higher risk of death or persistent organ dysfunction at 28 days.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The LOVIT-COVID and REMAP-CAP harmonized randomized clinical trials and the LOVIT trial, all of which studied administration of high-dose vitamin C (200 mg/kg/d) in patients with COVID-19 infection and sepsis, respectively, do not directly address this safety question. In these trials, administration of thiamine and other vitamins was at the discretion of the clinicians.…”
mentioning
confidence: 99%